Pelatihan Aplikasi Animasi Tux Paint Online Pada Pengurus Daerah Himpaudi Kecamatan Batam Kota - Nofriani Fajrah; Tukino Tukino; Baru Harahap (LPPM Universitas Putera Batam, 2022)
The development of Early Childhood Education institutions in various forms of Early Childhood Education services such as: TK, KB, TPA, SPS shows the increasing awareness of the community about the importance of education according to the stage of development from an early age. The increase in the number of Early Childhood Education service institutions is followed by the need for an increase in the number of PAUD educators. The need for educators is not only related to the number but also related to quality. Coaching educators in relation to increasing the ability of educators to provide early childhood education services that are in accordance with the needs of children's growth and development is a step taken by the Directorate of Early Childhood Education Development. Coaching is carried out through various strategies and practical activity programs. One of the patterns of fostering PAUD educators and education personnel is through the Early Childhood Education Cluster (PAUD Group). The Early Childhood Education Cluster is a strategic forum built from, by and for educators and education staff. Management, programs, forms of activities are planned, developed, and implemented to meet the needs of improving the teaching profession in accordance with the needs of members.